Going up - Kwok, Dylan (Nanyang Technological University, 2024)
This document describes the development journey of the mobile game Going Up, detailing the process from start to finish, with a particular focus on concept development, designing aesthetics to appropriately match the gameplay and the iterative design process of developing a game in consultation with playtesters.